Efeitos da experiência de eventos sobre a marca no contexto de uma instituição pública de ensino - Boing, Isabella Ramos (2020)
In the face of increasingly competitive markets, organizations seek to rethink their marketing practices and adopt new strategies to reach their target audience. As consumers are less receptive to traditional advertising, marketing managers have started to invest more in customer experiences. As a communication strategy, event marketing has become increasingly prevalent and can create extraordinary experiences for customers through these experiences, associating positive feelings to the brand. Thus, the objective of this research was to evaluate the effects of the experience of the scientific event on the brand of the promoting educational institution. To achieve the objective of this study, a self-administered questionnaire applied to students participating in the scientific event SEPEI, promoted by the Federal Institute of Santa Catarina, was used as a data collection instrument, resulting in a sample of 282 respondents. Data treatments were carried out through descriptive analysis to characterize the sample and verify the distribution of data for each research construct, using frequency analysis. Subsequently, Cronbach's Alpha, Composite Reliability and Average Variance Extracted tests were performed. Finally, Structural Equation Modeling was performed using the SPSS software with the AMOS extension, to verify the relationship between the model's constructs and analysis of the research hypotheses, which were supported. The results showed that the experience of the scientific event has an influence on brand experience, brand personality, brand reputation and brand loyalty of the promoting institution. It is concluded, then, that the experience of the scientific event has a positive effect on the brand of the promoting institution. This result demonstrates the relevance of new studies on the link between these constructs for the marketing area and, managerially, the importance of collecting information to support the communication and marketing strategies of educational institutions.